Does ESG initiatives yield greater firm value and performance? New evidence from European firms - Tahani Tahmid; Muhammad Nazmul Hoque; Jamaliah Said; Paolo Saona; Md. Abul Kalam Azad (Cogent Business & Management, 2022)
The environmental, social, and governance (ESG) factors are used to evaluate nonfinancial performance of a firm. While some researchers state that ESG initiatives taken by a firm increase its value and performance by lowering costs and unsystematic risks, others consider it as a wastage of firm resource. The purpose of this study is to put light to this ambiguity by examining the impacts of ESG initiatives on two aspects of a firm's success: its performance and its value. To test the study's hypothsis, a linear model with fixed effect GLS (generalized least squares) is used on a 12-year panel data set from 2008 to 2020 of 180 listed firms categorized in 10 economic sectors operating in 22 countries. Thomson Reuters ESG Score which measures a firm's ESG performance based on publicly available data, is used as an independent variable. As dependent variables the firm value and firm performance have been used. This study finds a positive impact of ESG initiatives on firm value and performance. It has been further observed that EU firms mostly focuses on social responsibilities of the ESG initiative due to its positive impact on firm's performance. Then the focus is given to environmental and governance initiatives respectively. The findings have far reached significance for researchers and firm executives helping them to understand the significance of ESG initiatives and effectively allocate and utilize firm's resources based on their importance.
Keywords: 650; Environmental Social and Governance score; ESG score; Firm performance; Firm value; ROA